Improving instruction through observation and feedback - Johnson, Todd.; Bittner, Ilana; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2002)
The improvement of instruction by using qualitative and quantitative observation techniques to collect classroom data
Tape 1. Different models of providing classroom-based assistance (34 min.) -- Tape 2. Observation techniques (23 min.) -- Tape 3. Approaches to working closely with teachers (34 min.)
Title from title screen
Editor, Ilana Brittner, Dave Brittner ; director of photography, Dave Brittner ; graphics, Dee Que, Dan Marsh Mike Johnson
Keywords: Observation (Educational method); Feedback (Psychology); Teachers -- Training of